Bibliometric Analysis of Students' Errors in Solving Problems on Sets using VOSviewer - Ginting, Adryani Br; Haryanza, Ajeng Sucitra; Zulkhoirunnisa, Alya; Amali, Ghina Rizki; Nadhira, Salma; Muntazhimah, Muntazhimah (FKIP Universitas Lampung, 2022)
Learning error can be interpreted as a certain condition marked by errors when someone completes a test. One of the causes of students' mistakes in answering questions is the lack of understanding of the concepts in the material. Research on student errors in solving problems related to set material uses the bibliometric method, which is still rarely done before. This research is indexed from Scholar with 500 articles obtained and extracted in the Publish or Perished (PoP) application. The articles obtained were published from 0 to 2022. The articles with the most article citations with 1837 citations occurred in 2020. After that, it was continued by visualizing the network, the number of cluster items was 10 red, 6 green and 4 blue, overlay and density by using the VOSviewer application. Therefore, it can be concluded that mathematical problem is one of the keywords that is still rarely studied. Keywords: students’ error, mathematics, bibliometric analysis, sets. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp766-773